Hubungan Kebiasaan Makan Dengan Kematangan Gonad Ikan Selar Kuning (Selaroides Leptolepis) yang Didaratkan Di Pelabuhan Perikanan Nusantara Sungailiat - Sriyanti Sriyanti; Wahyu Adi; Eva Utami (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Yellowstripe Scad (Selaroides leptolepis) has a high nutritional value and one of the foods that need to be preserved and conserved to support the needs of an increasing community, it is necessary to manage. This study aims to analyze food habits, food composition and gonadal maturity level (GML) as well as analyze the relationship of food habits with gonadal maturity of Yellowstripe Scad. Yellowstripe scad includes carnivorous fish. Percentage of IP of Yellowstripe Scad male food with main food is Clausocalanus arcuicornis 57,17%, supplementary food that is Copepoda 38,52% and the rest is complementary food with total 4,3%. Percentage of IP of Yellowstripe Scad female food with main food Clausocalanus arcuicornis and Copepoda with value respectively 54.57% and 42,56%, and the rest is complementary food with total 2.8%. At GML II, the amount of food eaten by male and female fish is small and there is little food variation. GML III, the amount of food eaten by male and female fish more and very much variation of food compared to GML II and IV. GML IV, the number of organisms eaten by male and female fish is very large and varied.